2012
DOI: 10.14430/arctic4182
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Investigations of Alpine Ice Patches in the Selwyn Mountains, Northwest Territories, Canada

Abstract: Inspired by the groundbreaking investigation of ice patch archaeology in Yukon Territory, the authors began exploring the Mackenzie, Selwyn, and Richardson Mountains for ice patch archaeological sites in 2000. Through remote sensing analysis, followed by intensive field surveys in the Selwyn and Mackenzie Mountains, we documented eight ice patch sites containing well-preserved archaeological artifacts and biological specimens. Twenty additional ice patches exhibit the key indicators of ice patch archaeological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Language can also provide clues to the histories of the caribou through descriptions like ɂekwewa "the original or prototypical caribou" that is used in Deĺınę to refer to barren-ground caribou and inform alternative ways of classifying the relationships between caribou types. Although it is difficult to determine the exact time-frame reflected in the language, it is well established that Dene people have a substantial history with caribou, and barren-ground caribou in particular have been a crucial and relatively consistent resource for at least the last 8000 years (Gordon 2003, Andrews et al 2012b, Beaulieu 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Language can also provide clues to the histories of the caribou through descriptions like ɂekwewa "the original or prototypical caribou" that is used in Deĺınę to refer to barren-ground caribou and inform alternative ways of classifying the relationships between caribou types. Although it is difficult to determine the exact time-frame reflected in the language, it is well established that Dene people have a substantial history with caribou, and barren-ground caribou in particular have been a crucial and relatively consistent resource for at least the last 8000 years (Gordon 2003, Andrews et al 2012b, Beaulieu 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Saami can routinely approach and harvest reindeer at these locations. Ion and Kershaw (1989) have noted similar caribou behavior in the Northwest Territories, and Andrews et al (2012a) have demonstrated overlap between the summer movement of radio-collared caribou and ancient ice patch hunting stands.…”
Section: Ice Patch Identification and Surveymentioning
confidence: 92%
“…High latitude and mountainous settings are prerequisite for these rare contexts, but not all regions seem to exhibit them in equal abundance. Particularly rich areas include British Columbia [44], southern Yukon Territory [43] and Northwest Territories [45,46] in Canada, areas of interior Alaska [47,48] and the Rocky Mountains in the western United States [49], and portions of Scandinavia and the European Alps [50]. The significance of ice patch finds stems from their ability to provide unique insights into prehistoric cultural developments and technology since these perishable items are rare in the vast majority of archaeological contexts.…”
Section: An Alpine Ice Field In Gates Of the Arctic National Park Andmentioning
confidence: 99%